Agribusiness opportunities of potatos in Gujarat - Panigrahy, Shakti Ranjan; Kalamkar, S S (Indian Farming, 2021)
Potato is a favourite vegetable and glory like gold that impacts different stakeholders throughout India and more specifically in Gujarat as this state contribute on the highest rung of the ladder in productivity. Banaskantha district holds the number one position in potato production in India. Holistic Policy environment, entrepreneurial culture, established infrastructure and business acumen of the producers’ communities transform potato as a crop into an agribusiness based commodity in Gujarat. Gujarat is a hub of many processing industries. This state is recognised for its processed varieties of potatoes that mean for French fries production. Amicable climatic condition at the time of harvest of potatoes helps in bumper production in this state. In a nutshell, Gujarat is a state that provides a sound business ecosystem for potato production in the era of agribusiness.